2013
DOI: 10.2332/allergolint.12-oa-0439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Interleukin 33 (IL-33) in Patients with Eosinophilic Pneumonia

Abstract: The remarkable increase of BALF IL-33 in AEP indicated the local production of IL-33 in lungs. IL-33 is considered to be a local key molecule for triggering pulmonary eosinophilia, together with IL-5. BALF IL-33 appears to be a useful marker for discriminating AEP from CEP and ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
5
22
0
Order By: Relevance
“…The serum and BAL levels of IL-33 were significantly higher in patients with acute eosinophilic pneumonia than in chronic eosinophilic pneumonia. 90 Consistent with this study, Ampawong et al recently demonstrated that bronchial IL-33 levels were increased in severe malaria patients with lung injury. 91 Acute Plasmodium falciparum infection increased eosinophil activity, 92 suggesting that IL-33 may play a role in lung injury with eosinophilic lung inflammation.…”
Section: Il-33/st2 In Alisupporting
confidence: 89%
“…The serum and BAL levels of IL-33 were significantly higher in patients with acute eosinophilic pneumonia than in chronic eosinophilic pneumonia. 90 Consistent with this study, Ampawong et al recently demonstrated that bronchial IL-33 levels were increased in severe malaria patients with lung injury. 91 Acute Plasmodium falciparum infection increased eosinophil activity, 92 suggesting that IL-33 may play a role in lung injury with eosinophilic lung inflammation.…”
Section: Il-33/st2 In Alisupporting
confidence: 89%
“…The serum IL-5 level decreased to zero after 10 days of treatment, even in one patient whose level was as high as 2448.0 pg/mL upon initial presentation. IL-5 is a specific cytokine that plays important roles in the recruitment, degranulation, and survival of eosinophils, and previous studies have demonstrated elevated IL-5 levels in both the serum and BAL fluid of patients with active AEP [13,15]. However, previous studies did not show serial changes with clinical improvement.…”
Section: Discussionmentioning
confidence: 89%
“…The concentration of IL-33, an epithelial cell-derived cytokine, in response to nonspecific stimuli and involved in innate immune response [35-37], is upregulated in BALF of EP patients [25, 26]. IL-33 can activate type 2 innate lymphoid cells (ILC2) to produce IL-5 or IL-13 [35, 36, 38], thereby inducing periostin.…”
Section: Discussionmentioning
confidence: 99%
“…As for the degree of cytokine/chemokine production in the airway, several reports suggest that the cytokine/chemokine concentrations are higher in AEP than in CEP, although the BALF eosinophil count of both is similar [20-26]. In fact, the IL-5 and IL-13 concentrations in BALF have been shown to be higher in AEP than in CEP [20-25]. Furthermore, compared with CEP, in AEP there is upregulated airway production of chemokines (e.g., eotaxin) for the activation of eosinophils, and of epithelial cell-derived cytokines (including IL-33) for the induction of the T2 response [23-26].…”
Section: Introductionmentioning
confidence: 99%